Investigation into the voltammetric behaviour and detection of selenium(IV) at metal electrodes in diverse electrolyte media - Beni, V.; Collins, G.; Arrigan, Damien (Elsevier BV, 2011)
The voltammetric behaviour of selenium(IV) was studied at platinum and gold electrodes in sulphuric acid, perchloric acid and potassium chloride media as a basis for its voltammetric detection. The best voltammetric behaviour was recorded at gold electrodes with perchloric acid as the supporting electrolyte. The concomitant presence of metals, such as copper or lead, and of model biomolecules, such as bovine serum albumin, in the solution resulted in a deterioration of the electrochemical response for selenium(IV). Quantitative detection of selenium(IV) by square wave anodic stripping voltammetry at both a millimetre-sized gold disc electrode and a microband electrode array revealed linear responses to selenium concentration in the ranges of 5-15 μM and 0.1-10 μM, respectively, with 60 s preconcentration. The sensitivities were 6.4 μA μM-1 cm-2 and 100 μA μM-1 cm-2 at the disc and the microband array, respectively. The detection limit at the microband electrode array was 25 nM, illustrating the potentiality of such microelectrodes for the development of mercury-free analytical methods for the trace detection of selenium(IV).